Analysis of Design Considerations for a 6 DoF Mobile Manipulator Based on Manipulability Measure - Mathew, Shyju Susan; R, Jisha V (Universitas Muhammadiyah Yogyakarta, 2025)
Mobile manipulators are highly versatile and are used across various fields due to their flexibility, reach, and adaptability. Hence it finds applications that involve complex environments or require high precision. The mobile manipulation tasks require the manipulators to retain good manipulation capability, which calls for reasonable motion planning. Manipulability, a crucial metric indicating the robot’s ability to perform effective and efficient manipulation tasks, serves as the central criterion for the design of redundant mobile manipulators (MM). In addition to this, for applications where the mobile base and manipulator are moving simultaneously, a design configuration with good manipulability measure is preferred. This study fills a significant gap in the literature by offering an analysis of the design considerations for a redundant MM for improved manipulability measure. In this paper, the end effector of a 6 DoF MM is made to move through a predefined trajectory, and the manipulability measure and manipulability ellipsoid are computed at various points in the workspace. The analysis is done based on various link length ratios, mounting positions of the arm, and mobile base speeds. The manipulability ellipsoids at various locations in the task space were analyzed which is indicative of maximum and minimum velocities achievable by the end effector. Based on the analysis, the best configuration is identified and a kinematic controller is designed for this configuration which traces the reference trajectory with high manipulability. An exhaustive simulation study shows the benefits of the suggested design principles and control techniques, reaffirming the significance of optimized link lengths, mounting positions, and mobile base speeds in enhancing manipulability. Although this study is carried out in a 6 DoF MM, the novelty of this research lies in its emphasis on enabling design of redundant MM for better manipulability which lays a strong foundation for future applications.